Community-acquired methicillin-resistant Staphylococcus aureus (CA-MRSA): molecular background, virulence, and relevance for public health - Bonesso,MF (2011)
Staphylococcus aureus and coagulase-negative Staphylococcus (CoNS) are frequently found in nosocomial environments as the main pathogen in several infections. In 1961, reports of nosocomial S. aureus resistant to methicillin, the drug of choice against penicillin-resistant strains, required new alternatives and vancomycin started being used to treat infections caused by methicillin-resistant S. aureus (MRSA). Community-acquired methicillin-resistant S. aureus (CA-MRSA) was first reported in 1990 affecting patients without risk factors for infection with MRSA of hospital origin. MRSA of community origin harbor the genes responsible for the synthesis of Panton-Valentine leukocidin (PVL), a toxin associated with skin and soft tissue infections and that carries the staphylococcal cassette chromosome mec (SCCmec) type IV. CA-MRSA emergence has caused great impact on the worldwide medical community since the presence of this pathogen in patients without risk factors represents a high risk to public health.